Boxing: an issue of medical ethics? - Spinsanti, Sandro (Medicina e Morale, 2024)
The ring kills. Without producing carnage like road traffic, it is nevertheless fatal for a considerable number of boxers. According to statistics, 357 boxers have fallen victim to the ring since the war, with an annual average of ten boxers, amateurs and professionals. A trickle, a slow haemorrhage. Enough, however, to ask whether something can or should be done to prevent those deaths. When a boxer falls into a coma or dies in the course of a fight, the controversy between boxing abolitionists and anti-abolitionists flares up for a moment; then the issue slips out of the field of interest, and is soon forgotten.